Analisis Penerimaan dan Pengelolaan Pajak Bumi Dan Bangunan dalam Meningkatkan Pendapatan Asli Daerah Kota Binjai - Anjali Damayanti; M. Rizaldy Wibowo (Jurnal Mirai Management, 2023)
This research aims to determine the receipt of Land and Building Tax in increasing the Original Regional Income of Binjai City. To determine the level of effectiveness of Land and Building Tax (PBB) Revenue in increasing Binjai City's Original Regional Income (PAD) by looking at the size of its contribution. This research uses qualitative research with descriptive research. The type of data used is secondary data. Secondary data includes interviews with sources. The data collection technique uses qualitative descriptive analysis, namely an analysis technique that does not use numerical or statistical data. The research results obtained are that Land and Building Tax revenue on Original Regional Income is very influential, and the contribution of Land and Building Tax revenue in Binjai City in increasing Regional Original Income is categorized as effective with an average of 57.28%, with a contribution in 2018 of 10.18%, in 2019 it was 11.39%, in 2020 it was 10.41%, in 2021 it was 13.09%, in 2022 it was 12.21%. Key words: PBB revenue, Regional Original Income